New Realization of Quadrature Oscillator using OTRA - Gurumurthy Komanaplli; Neeta Pandey; Rajeshwari Pandey (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper a new, operational transresistance amplifier (OTRA) based, third order quadrature oscillator (QO) is presented. The proposed structure forms a closed loop using a high pass filter and differentiator. All the resistors employed in the circuit can be implemented using matched transistors operating in linear region thereby making the proposed structure fully integrated and electronically tunable. The effect of non-idealities of OTRA has been analyzed which suggests that for high frequency applications self-compensation can be used. Workability of the proposed QO is verified through SPICE simulations using 0.18μm AGILENT CMOS process parameters. Total harmonic distortion (THD) for the proposed QO is found to be less than 2.5%.The sensitivity, phasenoise analysis is also discussed for the proposed structure.